Reconsiderations about the clinical importance of the sympathetic skin response - Resende, Luiz Antonio de Lima [UNESP]; Matarazzo, A. T. [UNESP]; Kimaid, P. A T [UNESP]; Silva, M. D. [UNESP] (My University, 1997)
Over the last few years, neurologists have been showing increasing interest in the study of the sympathetic skin response (SSR). In the present report we describe a simple method that permitted us to determine a wide variation of SSR in response to different stimuli such as respiration, deglutition, blinking, skeletal movements, biting, auditory or light stimuli, vocalization, and sphincter contraction. These results raise doubts about the role of SSR as a complementary diagnostic method.
Keywords: adult; amyotrophic lateral sclerosis; auditory stimulation; bite; blinking; breathing; diagnostic test; electrostimulation; female; human; human experiment; light; male; neurologic disease; neurophysiology; normal human; peripheral neuropathy; skin nerve; sphincter; swallowing; sympathetic tone; vocalization; Acoustic Stimulation; Adult; Blinking; Deglutition; Female; Galvanic Skin Response; Humans; Male; Movement; Muscle Contraction; Muscle, Skeletal; Phonation; Photic Stimulation; Respiration; Sympathetic Nervous System